Avaliação da meta de sustentabilidade da Agenda 2030 : um estudo sobre o acesso à água potável e à rede de esgoto dos estados brasileiros e dos municípios sergipanos - Santos, Daniela Barbosa dos (2019)
The basic building in the same events to events events, debates, seminários and palestras, foco de seeking the find problem solutions to the problems advindos the absence of tal service. This problem programmes for the capacity of the public public community in the public site in the site of a governança social, in the 12 doors ambiental, econômica, política e cultural. Tal modelo de desenvolvimento para o planejamento e gerenciamento de ações e ações em 2016 foi adotado como uma das metas dos processos de desenvolvimento sustentável, também conhecido como Agenda 2030. The present study had as objective to evaluate the distance to reach the goal of the Agenda 2030 of indicators of access to potable water and sewage network of residences of the federal states of Brazil and the municipalities of the state of Sergipe. Based on the indicators proposed by the Sustainable Public Management Guide developed by the Sustainable Cities Program and the indexes of the goals of the Sustainable Development Objectives. The research was based on the collection of secondary data regarding the quantity of active water supply connections and the number of connections in the sewage network in households in the states of the Brazilian federation and in Sergipe municipalities. The databases of the National Sanitation Information System (SNIS), the demographic census prepared by the Brazilian Institute of Geography and Statistics (IBGE), and the calculation formulas for indicators and indices of the Sustainable Cities Program and the Sustainable Development, respectively. The results were initially analyzed in Excel and then exported to QGIS 2.18 software in order to construct maps with the indexes indicating the distance to the Agenda 2030 target. The chosen indicators were: a) permanent and sustainable access to drinking water and; b) sewage network. It can be concluded that the present research allowed to evaluate in an integrated way the indicators and the sustainability goals of the Brazilian states and the municipalities of Sergipe and to verify in which situation they are faced with the goals determined by Agenda 2030. It is expected that this study be a reference for other studies on the subject, contribute to the dissemination of the Sustainable Cities Program and assist the public administration for improvements from the proposed public policies.